2018
DOI: 10.1172/jci95802
|View full text |Cite
|
Sign up to set email alerts
|

Hippo-mediated suppression of IRS2/AKT signaling prevents hepatic steatosis and liver cancer

Abstract: IntroductionNAFLD is characterized by an excessive accumulation of fat in the liver. The most severe form of NAFLD, NASH, often progresses to liver cancer (1-3). Tracking with the increasing prevalence of general obesity, 30% of the US population is now estimated to have NAFLD, and 25% of these individuals will develop NASH (1, 3). Currently, there are no effective therapies to prevent the incidence and progression of NAFLD or NASH (4). This makes clarification of the detailed mechanisms of disease progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(121 citation statements)
references
References 55 publications
3
102
5
1
Order By: Relevance
“…In response to organ injury, there is a complex dance that cells orchestrate to result in functional regeneration. YAP/TAZ have a long‐established role in regulating cell proliferation and survival and are increasingly being recognized to have other roles such as controlling cellular metabolism . These primarily are cell‐autonomous activities, but proper organ regeneration also requires coordinating critical non‐cell‐autonomous activities, including the removal of dead/dying cells, generation of extracellular matrices, and defining cell/organ polarity.…”
Section: Discussionmentioning
confidence: 99%
“…In response to organ injury, there is a complex dance that cells orchestrate to result in functional regeneration. YAP/TAZ have a long‐established role in regulating cell proliferation and survival and are increasingly being recognized to have other roles such as controlling cellular metabolism . These primarily are cell‐autonomous activities, but proper organ regeneration also requires coordinating critical non‐cell‐autonomous activities, including the removal of dead/dying cells, generation of extracellular matrices, and defining cell/organ polarity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 97 ] Whole liver Albumin‐Cre Pten flox/flox Sav flox/flox double knockouts rapidly developed HCC tumors within 5 months and this phenotype was suppressed to normal size by crossing with Yap flox/flox and Taz flox/flox to produce a quadruple knockout. [ 98 ] Hydrodynamic transfection of both PI3K ( PIK3CA H1047R ) and Yap S127A also produced HCC. [ 99 ] Furthermore, expression of strongly active Yap 5SA by hydrodynamic transfection of livers was sufficient to induce large HCC‐like tumors within 5 months and to recruit type II macrophages to induce immune evasion, which was required for tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, YAP knockout completely abrogated the regenerative capacity of rodent hepatocytes, highlighting the crucial role of Hippo signaling in controlling liver regeneration (Pepe‐Mooney et al, ). Interestingly, previous studies had also shown that suppression of IRS2/AKT by Hippo signaling can protect against steatosis and liver cancer progression (Jeong et al, ) and found YAP increased in multiple NAFLD models, in which expression and accumulation of YAP correlated with hepatocyte injury severity (P. Chen et al, ; Jeong et al, ; Kodama et al, ; Machado et al, ).…”
Section: Liver Cis‐regulatory Networkmentioning
confidence: 96%